Misfolded N-CoR is Linked to the Ectopic Reactivation of CD34/Flt3-Based Stem-Cell Phenotype in Promyelocytic and Monocytic Acute Myeloid Leukemia - Nin, Dawn Sijin; Li, Feng; Visvanathan, Sridevi; Khan, Matiullah (Frontiers in Oncology, 2015)
Nuclear receptor co-repressor (N-CoR) is the key component of generic co-repressor complex essential for the transcriptional control of genes involved in cellular hemostasis. We have recently reported that N-CoR actively represses Flt3, a key factor of hematopoietic stem cells (HSC) self-renewal and growth, and that de-repression of Flt3 by the misfolded N-CoR plays an important role in the pathogenesis of promyelocytic and monocytic acute myeloid leukemia (AML). The leukemic cells derived from the promyelocytic and monocytic AML are distinctly characterized by the ectopic reactivation of stem cell phenotypes in relatively committed myeloid compartment. However, the molecular mechanism underlying this phenomenon is not known. Here, we report that N-CoR function is essential for the commitment of primitive hematopoietic cells to the cells of myeloid lineage and that loss of N-CoR function due to misfolding is linked to the ectopic reactivation of generic stem cell phenotypes in promyelocytic and monocytic AML. Analysis of N-CoR and Flt3 transcripts in mouse hematopoietic cells revealed a positive correlation between N-CoR level and the commitment of myeloid cells and an inverse correlation between N-CoR and Flt3 levels in primitive as well as committed myeloid cells. Enforced N-CoR expression in mouse HSCs inhibited their growth and self-renewal potentials and promoted maturation toward cells of myeloid lineage, suggesting a role of N-CoR in the commitment of cells of myeloid lineage. In contrast to AML cells with natively folded N-CoR, primary and secondary promyelocytic and monocytic AML cells harboring the misfolded N-CoR were highly positive for Flt3 and myeloid antigen-based HSC marker CD34. Genetic and therapeutic restoration of N-CoR conformation significantly down-regulated the CD34 levels in monocytic AML cells, suggesting an important role of N-CoR in the suppression of CD34-based HSC phenotypes. These findings collectively suggest that N-CoR is crucial for the commitment of primitive hematopoietic cells to cells of myeloid lineage and that misfolded N-CoR may contribute to transformation of committed myeloid cells through the ectopic reactivation of Flt3/CD34-based stem cell phenotypes in promyelocytic and monocytic AML. Moreover, these findings provide novel mechanistic insights into the formation of leukemic stem cells in subsets of AML and identify the misfolded N-CoR as a subtype-specific biomarker of AML.